Unveiling the global impact of hypertensive heart disease among individuals aged ≥ 65 years: metabolic risk factors and future projections for 2050 - An, Ning; Qian, Dingding; Xu, Weifeng; Wang, Bingyu (Frontiers in Nutrition, 2025)
BackgroundHypertensive heart disease (HHD) poses a substantial global public health burden, particularly among older adults. Characterizing its epidemiological profile and projecting future trends are crucial for informing targeted prevention and management strategies.MethodsUtilizing global burden of disease (GBD) 2021 data spanning 1990–2021, we estimated age-standardized rates of prevalence, mortality, and disability-adjusted life-years (DALYs) for HHD in individuals aged ≥65 years across 204 countries and territories grouped into 21 region. We employed multiple analytical approaches: Joinpoint regression analysis to evaluate changes in age-standardized rates over time. Assessment of the proportion of HHD mortality and DALYs attributable to specific risk factors, quantified using population attributable fractions (PAFs) based on GBD risk-outcome associations and theoretical minimum risk exposure levels (TMRELs). Identification of key drivers (population growth, aging, epidemiological changes) underlying observed changes in HHD deaths and DALYs globally. Application of the Bayesian age-period-cohort (BAPC) model to evaluate age, period, and cohort effects on HHD risk and to project future incidence and mortality up to 2050. Quantification of socioeconomic disparities in HHD burden using the slope index of inequality (SII) and concentration index (CI), evaluated in relation to the socio-demographic index (SDI). Frontier analysis assessed the association between HHD burden and SDI levels. Identification of regions with the largest potential for reducing HHD burden relative to their SDI peers. Estimates are presented as means with 95% uncertainty intervals (UIs).ResultsIn 2021, the global age-standardized prevalence rate of HHD was 148.32 (95% UI: 117.32, 186.28) per 100,000 population. The age-standardized mortality rate was 16.32 (95% UI: 13.76, 18.01) per 100,000, and the age-standardized DALYs rate was 301.58 (95% UI: 255.06, 332.06) per 100,000. Join-point analysis revealed an increasing trend in age-standardized prevalence rates between 1990 and 2021, while mortality and DALYs rates decreased. Decomposition analysis identified changes in epidemiological rates as the primary driver of the global increase in HHD deaths and DALYs over this period. Metabolic risks, particularly high systolic blood pressure, were significant contributors to HHD-related mortality and DALYs, with a pronounced impact in high-SDI regions. Regions including the United States and Taiwan (China) exhibited the highest effective disparity, indicating substantial potential for improving HHD management relative to their SDI. Projections using the BAPC model indicate a continued rise in HHD incidence and global deaths by 2050.ConclusionDespite declining mortality/DALYs, HHD burden grows in older adults globally. Rising prevalence and projected incidence/deaths demand enhanced prevention. Metabolic risk dominance (high-SDI regions) prioritizes blood pressure control. Marked inequalities [US, Taiwan (China)] reveal opportunities for optimized resource allocation. Findings support tailored strategies to mitigate HHD impact.